Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve the following system of equations using elimination:

[tex]\[
\begin{array}{l}
-2x + 3y = -8 \\
5x - 2y = -2
\end{array}
\][/tex]

A. [tex]$(2, -4)$[/tex]
B. [tex]$(2, 4)$[/tex]
C. [tex]$(-2, 4)$[/tex]
D. [tex]$(-2, -4)$[/tex]
E. No Solution
F. Infinite Solutions


Sagot :

Let's solve the given system of equations step-by-step using the Elimination method:

The system of equations is:
[tex]\[ \begin{array}{l} -2x + 3y = -8 \\ 5x - 2y = -2 \\ \end{array} \][/tex]

1. Multiply Each Equation:
To eliminate [tex]\( y \)[/tex], we need to make the coefficients of [tex]\( y \)[/tex] in both equations equal in magnitude but opposite in sign. Therefore, we'll multiply the first equation by 2 and the second equation by 3:

[tex]\[ \begin{aligned} &2 \times (-2x + 3y) = 2 \times (-8) \quad \Rightarrow \quad -4x + 6y = -16 \quad \quad \text{[Equation 1 multiplied by 2]} \\ &3 \times (5x - 2y) = 3 \times (-2) \quad \Rightarrow \quad 15x - 6y = -6 \quad \quad \text{[Equation 2 multiplied by 3]} \end{aligned} \][/tex]

2. Add the Two Equations:
Now add the two new equations to eliminate [tex]\( y \)[/tex]:

[tex]\[ \begin{aligned} (-4x + 6y) + (15x - 6y) &= -16 + (-6) \\ -4x + 15x + 6y - 6y &= -22 \\ 11x &= -22 \end{aligned} \][/tex]

Solve for [tex]\( x \)[/tex]:

[tex]\[ x = \frac{-22}{11} = -2 \][/tex]

3. Substitute [tex]\( x \)[/tex] Back into One of the Original Equations:
Use the first original equation to find [tex]\( y \)[/tex]:

[tex]\[ \begin{aligned} -2(-2) + 3y &= -8 \\ 4 + 3y &= -8 \\ 3y &= -8 - 4 \\ 3y &= -12 \\ y &= \frac{-12}{3} = -4 \end{aligned} \][/tex]

So, the solution to the system of equations is [tex]\( x = -2 \)[/tex] and [tex]\( y = -4 \)[/tex].

Therefore, the correct solution for the system of equations [tex]\( \begin{array}{l} -2x + 3y = -8 \\ 5x - 2y = -2 \end{array} \)[/tex] is:
[tex]\[ \boxed{(-2, -4)} \][/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.